한국 자동차산업의 기술지식 진화와 지식창출 네트워크 변화 - 정진성; Jinseong Jeong; 구양미; Yangmi Koo (한국경제지리학회지, 2025)
본 연구의 목적은 자동차산업의 환경 변화에 따른 기술 진화와 기술지식 창출의 행위자 및 지역 네트워크의 변화를 실증적으로 분석하는 데 있다. 기술융합 분석 결과, 자동차산업의 기술은 기계·금속 중심에서 전자·소프트웨어 등 이종 기술의 융합으로 진화하였다. 행위자 네트워크 측면에서는 선도기업 중심 구조가 유지되면서도, 2000년대 이후 비기업 행위자와 이종 기업이 참여하는 개방형 네트워크로 변화하고 있다. 지역 네트워크에서는 전통 제조업 중심지는 쇠퇴하고, 수도권·연구시설 집적지의 중심성과 함께 지역 간 협력의 비중이 증가하는 경향이 나타났다. 이러한 결과는 한국 자동차산업 혁신 네트워크의 구조적 변화를 보여주며, 향후 개방형 혁신 생태계 구축과 지역 간 협력의 강화가 산업 경쟁력 제고에 기여할 수 있음을 시사한다. The aim of this study is to empirically analyze how shifts in the environment of automotive industry drive both technological evolution and changes in actor- and region-level knowledge-creation networks. The analysis on technological convergence reveals that automotive technologies have evolved from a mechanical- and metal-based focus toward integration with electronics, software, and other heterogeneous fields. On the actor network side, while leading firms continue to occupy key roles, since the 2000s the network has transitioned into an open structure that includes non-firm actors and firms from adjacent industries. Regionally, traditional manufacturing hubs have declined, whereas the prominence of the Seoul metropolitan area and research-cluster locations has risen, accompanied by a growing share of inter-regional collaboration. These findings illuminate the structural transformation of Korea’s automotive innovation network and suggest that fostering an open innovation ecosystem and strengthening inter-regional cooperation will be critical levers for enhancing industrial competitiveness.